2017
DOI: 10.2166/wst.2017.387
|View full text |Cite
|
Sign up to set email alerts
|

Surface water polycyclic aromatic hydrocarbons (PAH) in urban areas of Nanjing, China

Abstract: The concentration, sources and environmental risks of polycyclic aromatic hydrocarbons (PAHs) in surface water in urban areas of Nanjing were investigated. The range of ∑PAHs concentration is between 4,076 and 29,455 ng/L, with a mean of 17,212 ng/L. The composition of PAHs indicated that 2- and 3-ring PAHs have the highest proportion in all PAHs, while the 5- and 6-ring PAHs were the least in proportion. By diagnostic ratio analysis, combustion and petroleum were a mixture input that contributed to the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Accompanying the decline in environmental quality in China, the concentration of pollutants in the environment is rapidly increasing. Pollutants, such as polycyclic aromatic hydrocarbons, which are represented by benzopyrene (BaP) [5,6,7,8,9,10,11] and the heavy metal contaminant cadmium (Cd) [12,13,14], pose serious threats to our environment and life due to their strong toxicity and carcinogenicity. In the late twentieth century and early twenty-first century, both the government and people in general began to realize the importance of the environment; as such, environmental protection was strengthened and a series of legal measures for environmental protection were enacted [15,16], as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying the decline in environmental quality in China, the concentration of pollutants in the environment is rapidly increasing. Pollutants, such as polycyclic aromatic hydrocarbons, which are represented by benzopyrene (BaP) [5,6,7,8,9,10,11] and the heavy metal contaminant cadmium (Cd) [12,13,14], pose serious threats to our environment and life due to their strong toxicity and carcinogenicity. In the late twentieth century and early twenty-first century, both the government and people in general began to realize the importance of the environment; as such, environmental protection was strengthened and a series of legal measures for environmental protection were enacted [15,16], as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Nanjing has severe environmental problems resulting from its fast‐growing population, traffic, and industrial production (Wang, Zhou, He, et al, ). Many researchers have found that contaminants are present in different environmental media in Nanjing and its neighboring region in recent years (Hu et al, ; Lin, Wu, Ma, & Su, ; Lin, Ma, & Xiong, ; Wang et al, ; Lou et al, ; Wang, Wu, Zhou, Shi, & Song, ).…”
Section: Methodsmentioning
confidence: 99%
“…A volume of 10 mL of a PAH mixture solution (Naph, 500 ng/mL; Acy, 1000 ng/mL; Ace, 500 ng/mL; Fluo, 50 ng/mL; Phen, 50 ng/mL; Ant, 50 ng/mL; Flt, 50 ng/mL; Pyr, 50 ng/mL; BaA, 50 ng/mL; Chry, 50 ng/mL; BbF, 50 ng/mL; BkF, 50 ng/mL; BaP, 50 ng/mL; DahA, 100 ng/mL; BghiP, 50 ng/mL; IcdP, 50 ng/mL in water) was placed into a 25 mL flask containing 10 mg of each material (Mt, Na-Mica-4, ODA-Mt, ODA-Mica-4, ODTMA-Mt and ODTMA-Mica-4). Note that the concentration levels were selected based on the concentration frequently measured for PAHs in environmental samples [43][44][45][46]. The mixture was stirred at 600 rpm for 24 h. Subsequently, the supernatants were filtered (0.45 µm nylon filter) and an aliquot of 20 µL was injected into the HPLC system.…”
Section: Adsorption Batch Experimentsmentioning
confidence: 99%